2006
DOI: 10.1111/j.1365-2516.2006.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status and IOTN interventions among young hemophiliacs

Abstract: Fifty-two young individuals suffering from severe haemophilia A and B volunteered to be compared with school- and college-going students for oral health status description and subsequent management. A total of 244 students (84.42% boys and 15.58% girls) with the age group of 13-23 years were divided into two groups, A and B (controls). The purpose of this study was to increase awareness about evidence-based dental practices by oral examinations followed by comparisons of periodontal health and prevalence of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 14 publications
(15 reference statements)
2
46
1
4
Order By: Relevance
“…A number of studies reported lower oral hygiene/plaque scores among CBD, although their gingival situation was similar. [17,20,22,24] The present study also investigated the impact of dental and oral health on aspects of oral health-related quality of life such as laughing, eating, emotional and social wellbeing. We could not find clear differences between CBD and controls in their OHR-QoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies reported lower oral hygiene/plaque scores among CBD, although their gingival situation was similar. [17,20,22,24] The present study also investigated the impact of dental and oral health on aspects of oral health-related quality of life such as laughing, eating, emotional and social wellbeing. We could not find clear differences between CBD and controls in their OHR-QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to this clinical examination, we could not detect more problems in occlusion, and molar Hypoplasia among CBD patients compared with controls. [24] An important issue in CBD is oral bleeding. The highly vascular oral cavity is a common site for haemorrhage in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gautus rezultatus palyginome su kitose šalyse atliktais tyrimais ir galime teigti, kad mūsų gauti duomenys sutapo su tyrimų, atliktų Didžiojoje Britanijoje ir Šiau-rės Airijoje, rezultatais [12,13]. Tai leidžia daryti prielaidą, kad Lietuvos HSV dantų būklė yra panašesnė į anglų ir airių negu į HSV iš tolimesnių ir mažiau išsivysčiusių šalių [14,15]. Analizuojant ėduonies rizikos veiksnius ir lyginant juos tarp tiriamųjų grupių, duomenys yra prieštaringi: nors ėduonies intensyvumas tarp HSV pieniniame sąkandyje buvo mažesnis, bet jie buvo iš žemesnės SES šeimų, nenaudojo tarpdančių siūlo, jų burnos higiena mažai skyrėsi nuo bendraamžių sveikųjų.…”
Section: Rezultatų Aptarimasunclassified
“…Ištyrus Šiaurės Airijos ir Didžiosios Britanijos HSV pieninio ir nuolatinio są-kandžio dantų ėduonies paplitimą, rezultatai parodė, kad hemofilijos grupėje dantų ėduonies intensyvumo indeksas KPI/kp buvo mažesnis negu kontrolinėje grupėje [12,13]. Priešingus rezultatus paskelbė Pakistano ir Egipto mokslininkai: HSV turėjo daugiau ėduonies pažeistų, plombuotų ir išrautų dantų, palyginti su kontroline grupe [14,15]. Tai galima paaiškinti ypatinga HSV priežiūra specializuotose multidisciplininėse klinikose bei dantų ėduonies profilaktika nuo pat gimimo, vykdoma išsivysčiusiose šalyse, ir daryti išvadą, kad hemofilija sergančiųjų burnos sveikata tiesiogiai priklauso ir nuo šalies, kurioje HSV gyvena, išsi-vystymo ir gerovės [13].…”
unclassified